Comparative Approach to Theory of Mantiqat al-Firāq of Martyr al-Sadr and Mantiqat al-‘Afw of Sheikh al-Qardāwī - Mahmood Akbari; Mysam khazaee; mohammad edki (مطالعات تطبیقی فقه و اصول مذاهب)
The occultation of the Infallible Imam (as) and the emergence of new events increased the Muslims’ need to know the legal (shar'ī) ruling regarding the newly-emerged cases. It made some Islamic scholars struggle to consider the Islamic worldview and to believe in an area free of legal ruling. In Imāmī jurisprudence, the contemporary jurist Martyr Sayed Mohammad Bāqir al-Sadr called it “Mantiqat al-Firāq” (Belt of Lacuna) and in Sunni jurisprudence, the Egyptian jurist Yusuf al-Qardāwī called it “Mantiqat al-‘Afw” (Belt of Permission). Based on the descriptive-analytical method, this research aims to compare the two theories to investigate and analyze their feature and ambiguities. These two theories have many differences and similarities with each other that can be examined. Examining these two theories, it may be concluded that both areas, which have been proposed with the aim of social justice and respect for the general interests of the society, and in its design, the universality and immortality of the Islamic Shari'a have been taken into consideration, are empty of legal required rulings. In order to fill this area, it is necessary to bring up specific criteria and standards to match them with the general principles and rules of Islam. In addition, both theories have shortcomings that must be amended and completed by their proponents or even critics in order to be applicable.